Quality of life scores differs between genotypic groups of patients with suspected hereditary hemochromatosis - Paula Fernanda Silva Fonseca; Rodolfo Delfini Cançado; Flavio Augusto Naoum; Carla Luana Dinardo; Guilherme Henrique Hencklain Fonseca; Sandra Fatima Menosi Gualandro; José Eduardo Krieger; Alexandre Costa Pereira; Pierre Brissot; Paulo Caleb Junior Lima Santos (BMC, 2018)
Abstract Background Hereditary hemochromatosis (HH) encompasses a group of autosomal recessive disorders mainly characterized by enhanced intestinal absorption of iron and its accumulation in parenchymal organs. HH diagnosis is based on iron biochemical and magnetic resonance imaging (MRI) assessment, and genetic testing. Questionnaires, such as SF-36 (short form health survey), have been increasingly used to assess the impact of diseases on the patient's quality of life (QL). In addition, different genotypes are identified as results of genetic tests in patients with suspected primary iron overload. In the present study, our aim was to evaluate whether domains of QL are different according to genotypic groups in patients suspected of HH. Methods Seventy-nine patients with primary iron overload were included and two genotypic groups were formed (group 1: homozygous genotype for the HFE p.Cys282Tyr mutation; group 2: other genotypes). Results Group 1 had higher means of plasma transferrin saturation (86 ± 19%) and serum ferritin (1669 ± 1209 ng/mL) compared to group 2 (71 ± 12%, 1252 ± 750 ng/mL, respectively; p = 0.001). Four domains were significantly different among groups 1 and 2: physical functioning (p = 0.03), bodily pain (p = 0.03), vitality (p = 0.02) and social functioning (p = 0.01). Conclusions Our main finding was that patients with p.Cys282Tyr homozygosity had a worse QL scenario assessed by SF-36, compared with patients with iron overload without the same genotype. Being aware of this relationship between genotypes and QL might be helpful in the overall management of patients suspected of hereditary hemochromatosis.